2019
DOI: 10.1186/s13195-018-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and dementia: a systematic scoping review

Abstract: BackgroundAlcohol use has been identified as a risk factor for dementia and cognitive decline. However, some patterns of drinking have been associated with beneficial effects.Methods and ResultsTo clarify the relationship between alcohol use and dementia, we conducted a scoping review based on a systematic search of systematic reviews published from January 2000 to October 2017 by using Medline, Embase, and PsycINFO. Overall, 28 systematic reviews were identified: 20 on the associations between the level of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
212
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(252 citation statements)
references
References 77 publications
10
212
2
5
Order By: Relevance
“…Recent research has helped elucidate the dose-response relationship between alcohol consumption and some of these outcomes showing that, rather than having protective effect, light to moderate alcohol intake is associated with an increased risk of stroke, other cardiovascular disease subtypes (excluding myocardial infarction), and all-cause mortality [1,2]. Comparable studies examining the doseresponse relationship between alcohol consumption and long-term cognitive outcomes are lacking [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has helped elucidate the dose-response relationship between alcohol consumption and some of these outcomes showing that, rather than having protective effect, light to moderate alcohol intake is associated with an increased risk of stroke, other cardiovascular disease subtypes (excluding myocardial infarction), and all-cause mortality [1,2]. Comparable studies examining the doseresponse relationship between alcohol consumption and long-term cognitive outcomes are lacking [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Rehm and colleagues recently reported an overview of twenty systematic reviews (published 2000-March 2018) that had examined the relationship between alcohol use and dementia or cognitive impairment [6]. Only one of the twenty reviews reported a dose-response analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest a U-shaped relationship between regular alcohol consumption and cognitive function: frequent heavy consumption decreases cognitive performance, whereas regular light and moderate consumption may have a protective impact (Gutwinski et al, 2018). Chronic heavy alcohol consumption can cause thiamine (vitamin B1) deficiency and lead to Korsakoff 's syndrome, characterised by symptoms including confabulation, disorientation, severe memory loss and amnesia (Arts et al, 2017;Rehm et al, 2019;Wiegmann et al, 2020).…”
Section: Lifestylementioning
confidence: 99%
“…Similarly, so-called "blackout" episodes, commonly associated with drinking large amounts of alcohol over short periods of time (Goodwin, Crane & Guze, 1969;White, 2003), are clearly largely defined by and associated with AA (White, 2003;Nelson et al, 2004;Perry et al, 2006), appearing to involve both the frontal lobe and hippocampal regions (White, 2003;Oscar-Berman et al, 2004;Alderazi & Brett, 2007;Vetreno, Hall & Savage, 2011;Wetherill, Schnyer & Fromme, 2012;Hermens & Lagopoulos, 2018). In particular, chronic alcoholism appears to act synergistically with the normal ageing process to exacerbate the memory and other cognitive deficits commonly resulting from the latter (Pfefferbaum et al, 1992;Kim et al, 2012;Sabia et al, 2014;Guggenmos et al, 2017;Rehm et al, 2019).…”
Section: Basal Forebrain Damage In Ad and Arbdmentioning
confidence: 99%